LOFAR observations of the quiet solar corona - GALLAGHER, PETER; Vocks, C.; Mann, G.; Breitling, F.; Bisi, M.M.; Dabrowski, B.; Fallows, R.; Krankowski, A.; Magdalenić, J.; Marqué, C.; Morosan, D.; Rucker, H. (My University, 2018)
Context. The quiet solar corona emits meter-wave thermal bremsstrahlung. Coronal radio emission can only propagate above that radius, Rω, where the local plasma frequency equals the observing frequency. The radio interferometer LOw Frequency ARray (LOFAR) observes in its low band (10–90 MHz) solar radio emission originating from the middle and upper corona. Aims. We present the first solar aperture synthesis imaging observations in the low band of LOFAR in 12 frequencies each separated by 5 MHz. From each of these radio maps we infer Rω, and a scale height temperature, T. These results can be combined into coronal density and temperature profiles. Methods. We derived radial intensity profiles from the radio images. We focus on polar directions with simpler, radial magnetic field structure. Intensity profiles were modeled by ray-tracing simulations, following wave paths through the refractive solar corona, and including free-free emission and absorption. We fitted model profiles to observations with Rω and T as fitting parameters. Results. In the low corona, Rω < 1.5 solar radii, we find high scale height temperatures up to 2.2 × 106 K, much more than the brightness temperatures usually found there. But if all Rω values are combined into a density profile, this profile can be fitted by a hydrostatic model with the same temperature, thereby confirming this with two independent methods. The density profile deviates from the hydrostatic model above 1.5 solar radii, indicating the transition into the solar wind. Conclusions. These results demonstrate what information can be gleaned from solar low-frequency radio images. The scale height temperatures we find are not only higher than brightness temperatures, but also than temperatures derived from coronograph or extreme ultraviolet (EUV) data. Future observations will provide continuous frequency coverage. This continuous coverage eliminates the need for local hydrostatic density models in the data analysis and enables the analysis of more complex coronal structures such as those with closed magnetic fields.
Keywords: Sun; Corona; Radio radiation; Waves; Solar wind